A Photoactivatable AIE Polymer for Light-Controlled Gene Delivery: Concurrent Endo/Lysosomal Escape and DNA Unpacking - Yuan, Youyong; Zhang, Chong-Jing; Liu, Bin (Angewandte Chemie International Edition, 2015)
Endo/lysosomal escape of gene vectors and the subsequent unpacking of nucleic acids in cytosol are two major challenges for efficient gene delivery. Herein, we report a polymeric gene delivery vector, which consists of a photosensitizer (PS) with aggregation‐induced emission (AIE) characteristics and oligoethylenimine (OEI) conjugated via an aminoacrylate (AA) linker that can be cleaved by reactive oxygen species (ROS). In aqueous media, the polymer could self‐assemble into bright red fluorescent nanoparticles (NPs), which can efficiently bind to DNA through electrostatic interaction for gene delivery. Upon visible light irradiation, the generated ROS can break the endo/lysosomal membrane and the polymer, resulting in light‐controlled endo/lysosomal escape and unpacking of DNA for efficient gene delivery. The smart polymer represents the first successful gene vector to simultaneously address both challenges with a single light excitation process. Special delivery! A photoactive polymeric gene delivery vector can concurrently escape from the endo/lysosome and unpack nucleic acids in cytosol in a single light irradiation process. The polymer, which comprises a fluorogen with aggregation‐enhanced‐emission characteristics and a linker that can be cleaved by reactive oxygen species, forms nanoparticles that bind DNA and are endocytosed by cells.